Hybridization of concentrated solar power plants with biogas production systems as an alternative to premiums: The case of Spain. (July 2015) - Colmenar-Santos, Antonio; Bonilla-Gómez, José-Luis; Borge-Diez, David; Castro-Gil, Manuel
Abstract: The present research explains and analyses a technically feasible and economically profitable alternative for concentrated solar power plants recently constructed in Spain. The proposed solution is hybridization with biogas. The method is more economical than investment in salt storage systems, used to improve operation time and a better electrical production control. This alternative proposes new income alternatives for plants by using residual heat in flue gases from boilers and in the cooling circuit in the power block, thereby achieving an effective reduction in the final cost of electric power generation. Current commercial technologies used in the bio-digestion process of organic waste are studied and practical cases that can be best integrated are analyzed. Presented case studies are presented for solar power plants without storage analyzing waste availability for biogas production. Areas with the greatest potential for the implementation of the proposed alternative and improvements aimed at increasing the overall performance of future hybrid plants are also determined, and an economic evaluation of the proposed solution versus salt storage is conducted. To improve research results a sensitivity analysis to evaluate the feasibility in different economic scenarios is performed. Results show that the proposed method of hybridization through the use of biogas provides an alternative solution for an important part of renewable generation power plants with a limited ability for dispatchability. In terms of environmental issues the solution places a value on certain types of waste that today, in addition to not being utilized properly, pose a serious problem for society. Highlights: Research analyzes CSP plants and biogas power plants in European Union and Spain. Hybridization in CSP plants with biogas produced with waste in the surroundings. Availability of residues that allow hybridization feasibility is studied. Research analyzes impact of hybridization in the current CSP plants. Hybridization achieves increased profitability and environmental advantages.